Bacterial Sexually Transmitted Infections New Findings, Diagnosis, Treatment, and Prevention - Laura Vică, Mihaela (Infectious Diseases, 2023)
Bacterial sexually transmitted infections (STIs) are among the most widespread infections worldwide, causing major health problems. Bacterial Sexually Transmitted Infections - New Findings, Diagnosis, Treatment, and Prevention is a collection of chapters written by experts in the field from all over the globe. It includes recent scientific knowledge and advances in various approaches to the diagnosis, control, treatment, and management of bacterial STIs, depending on available resources and facilities. It presents research from the literature as well as different viewpoints to open new perspectives in this field. It is designed to improve the knowledge of those interested in bacterial STIs and new methods for their diagnosis and treatment.